2001
DOI: 10.1128/jb.183.24.7094-7101.2001
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of Expression of Staphylococcus epidermidis Housekeeping Genes with Taqman Quantitative PCR during In Vitro Growth and under Different Conditions

Abstract: The aims of the present study were (i) to develop and test a sensitive and reproducible method for the study of gene expression in staphylococci and (ii) to study the expression of five housekeeping genes which are involved in nucleic acid metabolism (gmk, guanylate kinase; the dihydrofolate reductase [DHFR] gene), glucose metabolism (tpi, triosephosphate isomerase), and protein metabolism (the 16S rRNA gene; hsp-60, heat-shock protein 60) during in vitro exponential and stationary growth. A modified method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
2
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 39 publications
5
116
2
5
Order By: Relevance
“…Gene quantification was done on a 2 ml sample (purified cDNA or gDNA), 12.5 ml 26 Taqman PCR master mix (PE Applied Biosystems), 0.9 mM of each primer and 0.2 mM of the probe in a final volume of 25 ml. The thermal cycling conditions were as previously published (Vandecasteele et al, 2001). To allow gene quantification, a standard dilution of a known quantity of the plasmid was included in each run.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene quantification was done on a 2 ml sample (purified cDNA or gDNA), 12.5 ml 26 Taqman PCR master mix (PE Applied Biosystems), 0.9 mM of each primer and 0.2 mM of the probe in a final volume of 25 ml. The thermal cycling conditions were as previously published (Vandecasteele et al, 2001). To allow gene quantification, a standard dilution of a known quantity of the plasmid was included in each run.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 100 ml sterile distilled water purified with the RNeasy Mini kit (Qiagen) according to the manufacturers' instructions. Reverse transcriptase reaction was performed as described earlier (Vandecasteele et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…N gene transcript abundances were normalized based on gene length and expressed as a proportion of the abundance of transcripts matching the gene encoding RNA polymerase subunit B (rpoB), as has been done in studies of diverse bacteria (for example, Schumann et al, 2010;Ceja-Navarro et al, 2014;Dalsgaard et al, 2014;Eldholm et al, 2014). Although rpoB expression can vary (Vandecasteele et al, 2001), rpoB appears to be one of the more stably expressed housekeeping genes (Sue et al, 2004;Sihto et al, 2014). Furthermore, it has been shown that rpoB can be a proxy of bulk mRNA transcription level for bacteria (Milohanic et al, 2003;Sue et al, 2004)-rpoB-normalized values therefore reflect transcription of a target gene relative to a housekeeping gene under a given condition/sample.…”
Section: Molecular Analysismentioning
confidence: 99%
“…En effet, la variation du C T pour ces gènes entre la condition témoin et les conditions de phase stationnaire est la plus faible. Il faut souligner qu'une variation physiologique est toujours présente entre les phases exponentielle et stationnaire [20]. Pour la suite des expériences, le gène codant la D-lactate déshydrogénase (ldhD) a été retenu.…”
Section: Mise En Oeuvre De La Rt-pcr Quantitative En Temps Réelunclassified